74 Using a community-based participatory approach to develop a needs assessment on intimate partner violence and reproductive coercion among arab americans in southeast michigan. (19th September 2017) - Khan, Angubeen; Elabed, Layla; King, Elizabeth; Kusunoki, Yasamin
Abstract : Statement of purpose: Intimate partner violence (IPV) affects approximately 25% of women nationwide. Previous studies suggest 10% prevalence of IPV in an Arab community from the mid-western US IPV is also linked to increased risk of reproductive coercion (RC) and limited reproductive autonomy. Given the gap in knowledge regarding IPV and RC, and the sensitive nature of these topics, community-based participatory approaches (CBPR) will allow the university-based researchers to collaborate with the Arab American community to develop a needs assessment for IPV and RC. Methods: Following a CBPR approach, university-based researchers partnered with a community organisation that serves Arab-Americans in Southeast Michigan. Two focus groups with 21 providers were conducted to discuss IPV and RC in the community, the influence of culture and religion on family planning, and recommendations for future research and intervention development. Fifteen women from the community will also be recruited to participate in an in-depth interview. Results: Preliminary findings suggest that IPV and RC are often ignored, accepted, or kept private. Furthermore, IPV and RC were attributed to family norms within Arab culture, but not religious norms. Insufficient culturally sensitive education and community pressure to become pregnant soon after marriage were cited as reasons for lack of family planning in the Arab community. Conclusion: There is a need to assess prevalence of and attitudes around IPV and RC in the Arab American community given the existing gap in knowledge and anecdotal evidence reported by community stakeholders. A CBPR approach is also a feasible approach for the community-university collaboration and for obtaining community recommendations regarding the IPV/RC needs assessment. Significance: Using a CBPR approach, we can begin to conduct research in an area that has previously received little attention. The needs assessment will also offer new ideas for culturally tailored IPV and RC interventions for Arab Americans.